Higher order chromatin structure at the X-inactivation center via looping DNA - Tsai, Chia-Lun; Rowntree, Rebecca K.; Cohen, Dena E.; Lee, Jeannie T. (Developmental biology, 2008)
In mammals, the silencing step of the X-chromosome inactivation (XCI) process is initiated by the non-coding Xist RNA. Xist is known to be controlled by the non-coding Xite and Tsix loci, but the mechanisms by which Tsix and Xite regulate Xist are yet to be fully elucidated. Here, we examine the role of higher order chromatin structure across the 100-kb region of the mouse X-inactivation center (Xic) and map domains of specialized chromatin in vivo. By hypersensitive site mapping and chromosome conformation capture (3C), we identify two domains of higher order chromatin structure. Xite makes looping interactions with Tsix, while Xist makes contacts with Jpx/Enox, another non-coding gene not previously implicated in XCI. These regions interact in a developmentally-specific and sex-specific manner that is consistent with a regulatory role in XCI. We propose that dynamic changes in three-dimensional architecture leads to formation of separate chromatin hubs in Tsix and Xist that together regulate the initiation of X-chromosome inactivation.